Histone variants: deviants? - Kamakaka, R.T.; Biggins, S. (Genes & Development, 2005)
Histones are a major component of chromatin, the protein-DNA complex fundamental to genome packaging, function, and regulation. A fraction of histones are nonallelic variants that have specific expression, localization, and species-distribution patterns. Here we discuss recent progress in understanding how histone variants lead to changes in chromatin structure and dynamics to carry out specific functions. In addition, we review histone variant assembly into chromatin, the structure of the variant chromatin, and post-translational modifications that occur on the variants.